Exploring the Impact of Chat GPT on Higher Education: Advantages, Hurdles, and Prospective Research Avenues - Zohaib Hassan Sain; Victa Sari Dwi Kurniati (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2023)
This article explores the potential advantages and obstacles associated with the utilization of the generative AI model, Chat GPT, within the realm of higher education, considering the constructivist theory of learning. In this analytical study, five positive aspects of Chat GPT are discussed, including its capacity to facilitate adaptive learning, offer personalized feedback, support research and data analysis, provide automated administrative services, and contribute to the creation of innovative assessments. Conversely, the article highlights five challenges, such as concerns about academic integrity, issues related to reliability, the difficulty in evaluating and reinforcing graduate skill sets, limitations in assessing learning outcomes, and the potential presence of biases and falsified information in information processing. The argument presented emphasizes the need for caution among tertiary educators and students when employing Chat GPT for academic purposes to ensure its ethical, dependable, and efficient use. To address these concerns, the article puts forth several recommendations, such as prioritizing education on the responsible and ethical use of Chat GPT, devising new assessment strategies, tackling bias and falsified information, and integrating AI literacy into graduate skills. By carefully considering both the potential benefits and challenges, the integration of Chat GPT has the potential to enhance the overall learning experiences of students in higher education.